2022
DOI: 10.1111/jam.15615
|View full text |Cite
|
Sign up to set email alerts
|

Novel amikacin resistance genes identified from human gut microbiota by functional metagenomics

Abstract: Aims:The aim of this study was to evaluate the diversity and potential for horizontal transfer of amikacin resistance genes from the human gut. Methods and results:A library of human faecal microbiota was constructed and subjected to functional screening for amikacin resistance. In total, five amikacin resistance genes that conferred relatively high amikacin resistance, with minimum inhibitory concentrations (MICs) ranging from 64 to >512, were identified from the library, including a novel aminoglycoside acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…We further evaluated the ability of ONN4ARG to identify novel ARGs based on 13 recently experimentally validated ARGs. 7,26,27 We searched for these 13 ARGs with both the DeepARG and ONN4ARG models. The results showed that ONN4ARG recognized 12 of these 13 ARGs and correctly classified their type of resistance (Table S4).…”
Section: Systematic Evaluation and Comparisonmentioning
confidence: 99%
“…We further evaluated the ability of ONN4ARG to identify novel ARGs based on 13 recently experimentally validated ARGs. 7,26,27 We searched for these 13 ARGs with both the DeepARG and ONN4ARG models. The results showed that ONN4ARG recognized 12 of these 13 ARGs and correctly classified their type of resistance (Table S4).…”
Section: Systematic Evaluation and Comparisonmentioning
confidence: 99%